P64 The association between the natural environment and emotional, social and behavioural development: a study using the ALSPAC cohort. (26th August 2022) - Ferguson, Mark
Abstract : Background: Recent literature has shown that greenspace is often associated with developmental outcomes throughout childhood and adolescence, with child social, emotional and behavioural (SEB) development receiving particular attention. Despite increased interest, there remains a considerable disconnect between theories of causal pathways and exposure metrics. Geographic uncertainty also hinders our understanding, as do the lack of longitudinal studies which obscure the role that temporality plays. Setting: This doctoral research uses repeat measures of self-reported and geospatial data from the Avon Longitudinal Study of Parents and Children (ALSPAC), to address the aforementioned research gaps (Eligible sample = 10, 512). Methods: Future analyses will investigate associations between Strength and Difficulties total difficulties score (TDS) at 5 time points with a) neighbourhood greenness (NDVI) and maternal-reported outdoor time and b) greenspace availability and maternal-reported park visits. However, given the extensive social patterning of greenspace availability and access, this preliminary analysis explores relationships between key exposure metrics and maternal educational attainment. It also investigates how greenspace exposure varies through the early years of the ALSPAC cohort (age 0–11.8) using linear regression. This will inform future work using a Life Course of Place framework. Key variables were identified through a directed acyclic graph. These were accounted for through measures of maternal education, area deprivation, urbanisation, family adversity, maternal smoking status during pregnancy, maternal age at birth, child ethnicity, child sex, and birthweight. Results: NDVI exposures and visits to greenspace are variable over time, with social patterning by educational attainment. For example, non-linear associations between greenness and maternal education are observed at birth (NDVI at birth at 500m. Reference: Degree vs no education: coefficient: 0.001 (-0.005, 0.008; p=0.67)). However increasingly strong linear associations are observed at later time points birth (NDVI at 11 years at 500m. Reference: Degree vs no education: coefficient: -0.032 (-0.038, -0.025; p=<0.001)). These early results indicate there is time-varying confounding and inequalities in childhood greenness exposure. This is prescient, as early life course analyses suggest that the strength of associations are non-sequential, indicating potential sensitive periods in childhood ((NDVI at birth at 500m vs TDS at 3.9 years: coefficient: -0.996 (-2.034, 0.042; p=0.060)) (NDVI at birth at 500m vs TDS at 11.8 years: coefficient: -2.077 (-3.365, -0.789; p=0.002))). These early results reveal that cross-sectional work is likely to have failed to capture changing interactions with greenspace through childhood.